Contents of Hopes and Duties: A Linguistic Analysis - Vaughn, Leigh Ann (Frontiers in Psychology, 2018)
People in a prevention focus tend to view their goals as duties and obligations, whereas people in a promotion focus tend to view their goals as hopes and aspirations. The current research suggests that people’s attention goes to somewhat different experiences when they describe their hopes versus duties. Two studies randomly assigned participants (N = 953) to describe a hope versus duty. Specifically, Study 1 asked participants to describe a personal experience of pursuing a hope versus duty, and Study 2 asked participants to describe a current hope versus duty they had. I analyzed these descriptions with Linguistic Inquiry and Word Count 2015. Consistent with earlier research on regulatory focus, participants wrote more about positive outcomes when describing hopes and social relationships when describing duties. The current research suggests that the effectiveness of common regulatory focus and regulatory fit manipulations could depend on participants’ freedom to choose the experiences they bring to mind when they describe their hopes and duties.